2020
DOI: 10.1029/2020ms002266
|View full text |Cite
|
Sign up to set email alerts
|

New SOA Treatments Within the Energy Exascale Earth System Model (E3SM): Strong Production and Sinks Govern Atmospheric SOA Distributions and Radiative Forcing

Abstract: Secondary organic aerosols (SOA) are large contributors to fine particle mass loading and number concentration and interact with clouds and radiation. Several processes affect the formation, chemical transformation, and removal of SOA in the atmosphere. For computational efficiency, global models use simplified SOA treatments, which often do not capture the dynamics of SOA formation. Here we test more complex SOA treatments within the global Energy Exascale Earth System Model (E3SM) to investigate how simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 233 publications
1
18
0
Order By: Relevance
“…For the cloud condensation nuclei (CCN) size range in the remote troposphere (100-500 nm; Brock et al 2019) ATom showed that OA was nearly ubiquitous, and a major fraction of the remote aerosol, mostly of secondary origin and highly aged (Hodzic et al 2020). A detailed comparison with stateof-the-art current CCMs by the same authors showed that while model skill has improved over time, this improvement is partially due to cancelling errors in both the source and loss terms (Hodzic et al 2016(Hodzic et al , 2020Lou et al 2020). The inorganic fraction of very remote CCN, on the other hand, was highly acidic (typically pH < 0) and consisted mostly of sulfate, with important implications for the particle phase state, hygroscopicity, radiative and chemical properties and, by implication, for the representation of ammonia source in CCMs (Nault et al 2021).…”
Section: E781mentioning
confidence: 99%
“…For the cloud condensation nuclei (CCN) size range in the remote troposphere (100-500 nm; Brock et al 2019) ATom showed that OA was nearly ubiquitous, and a major fraction of the remote aerosol, mostly of secondary origin and highly aged (Hodzic et al 2020). A detailed comparison with stateof-the-art current CCMs by the same authors showed that while model skill has improved over time, this improvement is partially due to cancelling errors in both the source and loss terms (Hodzic et al 2016(Hodzic et al , 2020Lou et al 2020). The inorganic fraction of very remote CCN, on the other hand, was highly acidic (typically pH < 0) and consisted mostly of sulfate, with important implications for the particle phase state, hygroscopicity, radiative and chemical properties and, by implication, for the representation of ammonia source in CCMs (Nault et al 2021).…”
Section: E781mentioning
confidence: 99%
“…Our empirical function of BC absorption enhancement versus coating thickness implies strong absorption of solar radiation by ambient BC aerosol and allows for realistic representation of this effect in climate models as coatings develop with age. Most current treatments assume unrealistic BC morphology (Bauer et al., 2010; Jacobson, 2000; Koch et al., 2009; Lou et al., 2020) which can lead to very high estimates of BC absorption cross‐section (Bond et al., 2006) and overestimate the direct radiative effect. When the more realistic core‐shell morphology is assumed for BC particles it is common to assume homogeneity in BC core size and coating thickness (Chung et al., 2012; Jacobson, 2012; Yu, 2011) which we show will also lead to overestimates of BC absorption.…”
Section: Discussionmentioning
confidence: 99%
“…However, all models fail to capture this rapid change in SOA composition, regardless of the chemical aging process, indicating possible missing sources of SOA from biomass burning sources. Several studies reported that the GFED biomass burning emissions underestimate POA emissions (Lou et al., 2020) and also found that a simple empirical treatment that accounts for the aging of POA from biomass burning sources to form SOA shows good performance in simulating surface OA loadings (Lou et al., 2020). These implications call for additional sensitivity tests for the KORUS‐AQ period but are beyond the scope of this paper.…”
Section: Model Evaluation During Korus‐aqmentioning
confidence: 99%